Unlocking the potential of de-oiled seeds of Citrus sinensis loaded with metal nanoparticles for Congo red degradation and removal: a green water treatment strategy with bibliometric analysis - Tahira, Misbah; Batool, Fozia; Noreen, Sobia; Mustaqeem, Muhammad; Munawar, Khurram Shahzad; Kanwal, Samia; Shahbaz, Komal; Arshad, Anila; Ali, Hayssam M. (Frontiers in Sustainable Food Systems, 2024)
This research reported the utilization of novel adsorbent from the de-oiled waste material of orange seeds for preparing simple charcoal (SC) and iron oxide/activated charcoal (Fe2O3/AC) nanocomposites. Batch adsorption experiments were carried out to evaluate the optimized conditions of the experiment. The results obtained indicated that the pseudo-second-order kinetic model best fitted the adsorption data (R2 > 0.99) and that the Freundlich isotherm model best explained the adsorption of dye on Fe2O3/AC. The adsorption process was spontaneous and exothermic in the temperature range of 293–333°K, as explained by calculated thermodynamic parameters, e.g., ΔG°, ΔH°, and ΔS°. The Fourier transform infrared (FTIR) spectroscopy results publicized that carboxyl and amine functional groups are present on the surface of adsorbents, which are responsible for the attachment of dye. The scanning electron microscopy (SEM) results showed that Fe2O3/AC has a porous surface and textual structure, which can efficiently adsorb dye molecules. A zetasizer was utilized for determining the size of the composites, and the thermal stability was determined by performing a thermogravimetric analysis (TGA). The findings of the comparative experiment indicated that Fe2O3/AC are more promising than raw activated carbon for the adsorption of Congo red (CR). The impregnation of iron oxide nanocomposites on an adsorbent resulted in an increased surface area-to-volume ratio, magnetic properties, and excellent reusable capacity. Overall, it can be reported as an innovative procedure promoting the recycling of waste products, which aids in protecting environmental and human health and in the development of the economy.